Psychiatric disorders and comorbidity in a Spanish sample of prisoners at the end of their sentence: Prevalence rates and associations with criminal history - Pagerols, Mireia; Valero, Sergi; Dueñas, Lourdes; Bosch, Rosa; Casas, Miquel (Frontiers in Psychology, 2023)
Introduction This study examined, for the first time, the prevalence of mental disorders and comorbidities among inmates who were about to be released, and their association with criminal history. Methods A Spanish sample of 140 prisoners at the end of their sentence was recruited from an occupational program. Psychiatric disorders were determined according to the Diagnostic and Statistical Manual of Mental Disorders criteria. Bivariate analyses followed by multivariate regression models were conducted to identify significant variables for repeat incarceration and violent offending. Results The lifetime prevalence of Axis I disorders was 81.4%, with substance use disorders (SUD) and attention deficit/hyperactivity disorder (ADHD) being the most common diagnoses (51.4 and 31.4%, respectively). The current prevalence of Axis I disorders was 59.0%, including learning disorders (38.6%), ADHD (16.4%), and SUD (5.71%) among the most frequent syndromes. Thirty-six (26.5%) participants met criteria for a current Axis II disorder, which commonly was an antisocial personality disorder (12.5%). The majority of the sample (60.8%) suffered from two or more comorbid disorders during their lifetime, although the current prevalence fell to 23.3%. Childhood ADHD increased the number of imprisonments, while inmates convicted of a violent crime were more likely to present a learning disorder. Having a lifetime diagnosis of SUD or multiple psychiatric disorders appeared to be associated with both repeat incarceration and violent offending. Conclusion Given the high rate of mental disorders still present among subjects completing prison sentences and the challenges they may encounter to benefit from vocational programs, our results suggest that appropriate psychiatric care should be provided during imprisonment and after release to facilitate their community reintegration.